Investigation on the mechanical and water absorption properties of eco-friendly bricks produced from waste polypropylene (PP) Bumper - Ong, Hueiruey; Wan Mohd Eqhwan, Iskandar; Mohamad Abid, Yunos; Muhammad Faiz, Mohd Zaki; Khan, Md Maksudur Rahman; Hong, Chi Shein; Mohd Syahiful Adlan, Maarof; Nora Fandy, Ismail (Italian Association of Chemical Engineering - AIDIC, 2023)
Plastic waste is a growing environmental concern worldwide, and the development of sustainable solutions to manage plastic waste has become a critical priority. One promising solution is the conversion of plastic waste into useful products, such as bricks. This study investigates the potential use of waste polypropylene (PP) bumper, a common automotive plastic waste, to produce eco-friendly bricks. The waste PP bumper was collected from a local industry and mixed with sand in ratios ranging from 100 % PP to 40% PP. The produced bricks were subjected to compression, flexural, and water absorption tests. Results showed that the addition of sand to the PP waste bumper improved the mechanical and water absorption properties of the bricks. In particular, the plastic bricks with minimal inclusion of 5 % bitumen exhibited the highest compressive strength of 8.532 MPa and flexural strength of 1.287 MPa while maintaining low water absorption of 0.04 %. The results of this study suggest that waste PP bumper can be used as a viable raw material for eco-friendly brick production, and the optimal ratio of PP and sand can be determined based on the desired properties of the bricks. The future application of these eco-friendly bricks can be in construction projects in which able to replace traditional clay bricks and contribute to the reduction of plastic waste in landfills.